Parthenocarpic tomato mutants, iaa9-3 and iaa9-5, show plant adaptability and fruiting ability under heat-stress conditions - Mubarok, Syariful; Jadid, Nurul; Widiastuti, Ani; Derajat Matra, Deden; Budiarto, Rahmat; Lestari, Fitrianti Widya; Nuraini, Anne; Suminar, Erni; Pradana Nur Rahmat, Bayu; Ezura, Hiroshi (Frontiers in Plant Science, 2023)
Fruit set is one of the main problems that arise in tomato plants under heat-stress conditions, which disrupt pollen development, resulting in decreased pollen fertility. Parthenocarpic tomatoes can be used to increase plant productivity during failure of the fertilisation process under heat-stress conditions. In this study, we identified the plant adaptability and fruiting capability of iaa9-3 and iaa9-5 mutans under heat-stress conditions. The iaa9-3 and iaa9-5 and wild-type Micro-Tom (WT-MT) plants were cultivated under two temperature conditions: normal and heat-stress conditions. Under the heat-stress condition, iaa9-3 and iaa9-5 showed delayed flowering time, increased number of flowers and increased fruit set and produced normal-sized fruit. However, WT-MT cannot produce fruits under heat stress. The mutants can grow under heat-stress conditions, as indicated by the lower electrolyte leakage and H2O2 concentration and higher antioxidant activities compared with WT-MT under heat-stress conditions. These results suggest that iaa9-3 and iaa9-5 can be valuable genetic resources for the development of tomatoes in high-temperature environmental conditions.